(untitled) (Revista Argentina de Musicología, 2018)
Review: Pujol, Sergio. 2007. Las ideas del rock: genealogía de la música rebelde. Rosario: Horno Sapiens Ediciones, 187 págs. ISBN 978-950-808-523-8.